2022
DOI: 10.3389/fimmu.2022.855342
|View full text |Cite
|
Sign up to set email alerts
|

The Antioxidant, Anti-Inflammatory and Immunomodulatory Effects of Camel Milk

Abstract: Camel milk (CM) has been found to have several health benefits, including antiviral, antibacterial, anti-tumor, anti-fungal, antioxidant, hypoglycaemic and anti-cancer activities. In addition, CM can counter signs of aging and may be a useful naturopathic treatment for autoimmune diseases. The composition of CM varies with geographic origin, feeding conditions, seasonal and physiological changes, genetics and camel health status. In the present review, we collate the diverse scientific literature studying anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 99 publications
(131 reference statements)
0
14
1
Order By: Relevance
“…The inhibitory effect of camel milk against pathogenic micro-organisms is well known [ 76 ]. In addition, several bioactive compounds (lactoferrin, α-lactalbumin, β-caseins and vitamin C, lysozyme, IgG and secretory IgA, and insulin-like protein) present in camel milk exhibited antioxidant, anti-inflammatory and immunomodulatory properties [ 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…The inhibitory effect of camel milk against pathogenic micro-organisms is well known [ 76 ]. In addition, several bioactive compounds (lactoferrin, α-lactalbumin, β-caseins and vitamin C, lysozyme, IgG and secretory IgA, and insulin-like protein) present in camel milk exhibited antioxidant, anti-inflammatory and immunomodulatory properties [ 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our results can be explained from the work of Behrouz et al . 60 , Salwa 61 and Jihen et al . 62 , they reported that camel milk includes high quantities of antioxidants like vitamins A, E, and C as well as minerals like Zn, Se, and Mg that are linked to higher levels of glutathione, GPx, and SOD.…”
Section: Discussionmentioning
confidence: 97%
“…Besides these effects, CM possesses antiviral properties against hepatitis C virus, cytomegalo virus, rotavirus, herpes simplex virus-1 and human immunodeficiency virus [ 121 ]. Moreover, they have been reported to possess antifungal properties ( Candida albicans ); although much less literature is available in this regard [ 84 , 122 ]. It has been argued that these effects were mainly attributed to the presence of greater amounts of LF, LZ, Igs, NAGase, PGRPs and LP etc.…”
Section: Brief Overview Of Camel Milk (Cm) Componentsmentioning
confidence: 99%